The Correlation between Vital Statistics and Body Weight of Fat-Tailed Sheep at Different Ages in Gucialit Village, Lumajang Regency: Korelasi Statistik Vital dengan Bobot Badan Domba Ekor Gemuk pada Berbagai Umur di Desa Gucialit, Kabupaten Lumajang - Sholeh, Badrus; Ciptadi, Gatot; Diani, Khonita Rahma; Mudawamah, Mudawamah (BPFP Universitas Bengkulu, 2025)
This study aims to determine the correlation between vital statistics and body weight of fat-tailed sheep in Gucialit Village, Gucialit District, Lumajang Regency. This study used 72 fat-tailed sheep consisting of 36 male sheep and 36 female sheep. The sheep were grouped by sex and age into 6 groups, namely male sheep aged <12 months (PI0a), female sheep aged <12 months (PI0b), male sheep aged >12-18 months (PI1a), female sheep aged >12-18 months (PI1b), male sheep aged >18 months (PI2a) and female sheep aged >18 months (PI2b). The results showed that there was a positive correlation between chest circumference, shoulder height, and body length with body weight in all age and sex groups. Chest circumference had the strongest correlation with body weight in all age and sex groups. The highest correlation coefficient value between chest circumference and body weight was obtained in the PI2a group, which was 0.82, and the coefficient of determination (R²) was 68.1%. It can be concluded that chest circumference is the most suitable variable for estimating the body weight of fat-tailed sheep in Gucialit Village.